2009
DOI: 10.1039/b822776d
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen photosensitisation by the fluorescent probe Singlet Oxygen Sensor Green®

Abstract: The fluorescent probe Singlet Oxygen Sensor Green is able to produce singlet oxygen under exposure to UV or visible radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(189 citation statements)
references
References 22 publications
(27 reference statements)
9
178
0
2
Order By: Relevance
“…We used a widely used chemical trapping method for 1 O 2 detection following plasma treatment of fluid and E. coli. SOSGR is relatively stable in acidic pH (plasma causes slightly acidic pH), where it fluoresces bright green upon activation/ trap (3,4,18). Singlet oxygen sensor green reagent (SOSGR) has been successfully applied to animal cells, plant cells, and bacterial cells, such as Staphylococcus aureus (13), and to plasma engineering of 1 O 2 production (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a widely used chemical trapping method for 1 O 2 detection following plasma treatment of fluid and E. coli. SOSGR is relatively stable in acidic pH (plasma causes slightly acidic pH), where it fluoresces bright green upon activation/ trap (3,4,18). Singlet oxygen sensor green reagent (SOSGR) has been successfully applied to animal cells, plant cells, and bacterial cells, such as Staphylococcus aureus (13), and to plasma engineering of 1 O 2 production (31).…”
Section: Discussionmentioning
confidence: 99%
“…⅐ and does not show any appreciable response to hydroxyl radical ( ⅐ OH) or superoxide ( ⅐ O 2 Ϫ) (3,4,18). A 1 mM stock solution was freshly prepared in methanol (aliquoted and stored at Ϫ20°C in ambercolored microtubes), and a final working concentration of 1 M (i.e., 1:1,000 dilutions) was used in reaction solution after optimization.…”
Section: Omentioning
confidence: 99%
“…S20-S25, ESI †). 16,33,41 A comparison of the temporal evolution of 1 O 2 formation -as indicated by the increase of the SOSG photoluminescence signal -and the photobleaching kinetics in PTB7-Th (Fig. 5a-c) and PTB7 ( Fig.…”
Section: Nickel(ii) Dibutyldithiocarbamate Suppresses Singlet Oxygen mentioning
confidence: 99%
“…2B, panel iv). A drawback of SOSG is that it can act as a photosensitizer producing 1 O 2 upon exposure to UV radiation and, to a lesser extent, visible light (Ragàs et al, 2009). We exposed a SOSG solution to the light conditions used in this study (1500 mmol photons m 22 s 21 for 30 min), and we observed that SOSG fluorescence at 525 nm was slightly increased (Supplemental Fig.…”
mentioning
confidence: 99%